Kickboxer. Retaliation [videorecording (DVD)] - Moussi, Alain, 1981-; Lambert, Christopher, 1957-; Damme, Jean-Claude van, 1960- (Well Go USA Entertainment, 2018)
One year later, Kurt Sloan has vowed never to return to Thailand. However, while gearing up for a MMA title shot, he finds himself sedated and forced back into Thailand, this time in prison. He is there because the ones responsible want him to face a 6'8" 400 lbs. beast named Mongkut and in return for the fight, Kurt will get two million dollars and his freedom back. Kurt at first refuses, in which a bounty is placed on his head as a way to force him to face Mongkut.